The Impact of Using Geschool Application on Cultural Arts Learning (Dance) at Adabiah 2 Padang High School - Maharani, Bunga; Indrayuda (Universitas Negeri Padang, 2023)
This study aims to describe the impact of using the geschool application on cultural arts learning (dance) at Adabiah 2 Padang High School. The type of research used is qualitative research. The instrument of this research is the researcher himself, who is assisted by supporting instruments in the form of cameras, photographs, and interviews. The type of data uses primary and secondary data. Data collection techniques were carried out by means of literature study, observation, interviews, and documentation. The steps of analysing data are: identifying data, clarifying data, describing data, analysing data, and concluding data. The results showed that the use of the Geschool application in learning cultural arts (dance) in class XI MIPA 1 SMA Adabiah 2 Padang has a positive and negative impact on teachers and students. The positive impact for teachers is that it is easier for teachers to access material in school; there is a responsibility for daily exercises and tests for students. The negative impact on teachers is signal interference, which causes the school to error when sending material to students, health problems, and the teaching and learning process to be ineffective and inefficient. While the positive impact on students is discipline and responsibility for the tasks given by the teacher, students can repeat the material that has been taught at home. The negative impact on students is that they have difficulty understanding the material, parents' expenses are increasing to buy internet packages for learning at school and at home, threatening health, students are negligent with smartphones in learning, and there is a lack of student interaction with their friends.